Reproductive performance of captive Asian elephants (Elephas maximus) in large tourist camps in Thailand - Patiparn Toin (2020)
© 2020 Elsevier B.V. In Thailand, many elephants are used in tourism, with populations sustained by breeding of animals that are in captive habitats. Even though there are programs to promote breeding, there is not success in all camps. In this study, there was summarization of reproductive performance data of 407 elephants (150 males, 257 females) at seven tourist camps based on 4–21 years of breeding records. Age pyramid structures for elephants varied among camps. Reproductive rates averaged 21.6 ± 6.17% and varied among camps (2.8–45.0%). Based on parity, 77.4% of elephants were nulliparous, 8.2% produced one calf, and 14.3% were multiparous, with there being camp differences. There were 1.10 ± 0.46 (range, 0.03–3.55) births per year, with a total of 19.6 ± 9.3 (1–71) calves per camp. Age at first calving was 19.2 ± 1.1 years (range, 8–40 years), mean inter-birth interval was 4.4 ± 0.2 years (range, 1.8–7.9 years), and average gestation length was 653.9 ± 6.9 days (range, 578–743 days). Rates of abortions/stillbirths averaged 12.4% and ranged from 3.5%–66.7%. There were no obvious differences in management (e.g., number of males, estrous detection methods, work activities) that when evaluated explained the range in breeding success, although lack of male interest in females was a common problem. While informative and useful for designing future studies, results of this study indicate there is a lack of precise breeding records that makes it difficult to evaluate effects of management practices on reproductive performance of captive elephants in Thailand.